Exploring Resistance to Spiritual Emergence| A Heuristic Inquiry - Michelle, Katrina (Sofia University, 2017)
Spiritual emergence is a natural part of the human developmental experience. The process is unique to each individual and may gradually unfold or suddenly arise. Yet, because there is no mainstream cultural framework to provide context for the broad spectrum of anomalous experiences that may occur within it, there can be resistance to the process. The purpose of this exploratory study was to elucidate the phenomenon of spiritual resistance within the spiritual emergence process. Using the heuristic method, 18 participants who self-identified as having experienced spiritual resistance were interviewed. Based on data gathered through this research, 5 types of spiritual resistance and 11 ways of overcoming it were named. Spiritual resistance has both a protective and inhibiting function. Although at times it may serve to stifle the progression of spiritual development, it may also be the intermediary in protecting the ego from the tumultuous process experienced during spiritual emergency.